Common aquatic pollutants modify hemocyte immune responses in Biomphalaria glabrata - Lynch, Adam E.; Noble, Leslie R.; Jones, Catherine S.; Routledge, Edwin J. (Frontiers in Immunology, 2022)
Disruptions to reproductive health in wildlife species inhabiting polluted environments is often found to occur alongside compromised immunity. However, research on impacts of aquatic pollution on freshwater mollusc immune responses is limited despite their importance as vectors of disease (Schistosomiasis) in humans, cattle and wild mammals. We developed an in vitro ‘tool-kit’ of well-characterized quantitative immune tests using Biomphalaria glabrata hemocytes. We exposed hemocytes to environmentally-relevant concentrations of common aquatic pollutants (17-estradiol, Bisphenol-A and p,p’-DDE) and measured key innate immune responses including motility, phagocytosis and encapsulation. Additionally, we tested an extract of a typical domestic tertiary treated effluent as representative of a ‘real-world’ mixture of chemicals. Encapsulation responses were stimulated by p,p’-DDE at low-doses but were suppressed at higher doses. Concentrations of BPA (above 200 ng/ml) and p,p’-DDE (above 500 ng/ml) significantly inhibited phagocytosis compared to controls, whilst hemocyte motility was reduced by all test chemicals and the effluent extract in a dose-dependent manner. All responses occurred at chemical concentrations considered to be below the cytotoxic thresholds of hemocytes. This is the first time a suite of in vitro tests has been developed specifically in B. glabrata with the purpose of investigating the impacts of chemical pollutants and an effluent extract on immunity. Our findings indicate that common aquatic pollutants alter innate immune responses in B. glabrata, suggesting that common aquatic pollutants may be a critical, yet overlooked, factor impacting disease by modulating the dynamics of parasite transmission between molluscs and humans.